2000
DOI: 10.1046/j.1365-2761.2000.00222.x
|View full text |Cite
|
Sign up to set email alerts
|

Normal and aberrant tissue distribution of Loma salmonae (Microspora) within rainbow trout, Oncorhynchus mykiss (Walbaum), following experimental infection at water temperatures within and outside of the xenoma‐expression temperature boundaries

Abstract: Temperatures above 20°C or below 9°C interrupt the life cycle of the gill intracellular microsporidian parasite Loma salmonae (Microspora) prior to sporogony, inhibiting the production of xenomas. This study intended to characterize this life-cycle failure. Juvenile rainbow trout, Oncorhynchus mykiss (Walbaum), were experimentally infected with L. salmonae spores, and the effect of water temperature on the progress of infection, as determined by polymerase chain reaction, was compared for fish held at water te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 19 publications
(36 reference statements)
2
25
0
Order By: Relevance
“…Beaman et al (1999) found that normal development of Loma salmonae is interrupted by temperatures below 9°C as well as above 20°C, when xenoma formation in the gills is inhibited. At low temperature, the parasite arrives in the heart where an initial merogony normally occurs, but xenoma formation in the gills does not occur and the gills eventually become PCR-negative by 4 wk post-challenge (Sanchez et al 2000(Sanchez et al , 2001. Apparently, normal proliferation in the heart is arrested by low temperatures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beaman et al (1999) found that normal development of Loma salmonae is interrupted by temperatures below 9°C as well as above 20°C, when xenoma formation in the gills is inhibited. At low temperature, the parasite arrives in the heart where an initial merogony normally occurs, but xenoma formation in the gills does not occur and the gills eventually become PCR-negative by 4 wk post-challenge (Sanchez et al 2000(Sanchez et al , 2001. Apparently, normal proliferation in the heart is arrested by low temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Microsporidian development may be highly temperature-dependent (see Sanchez et al 2000). Kaba -tana takedai infections in salmonids do not develop at 9°C, and are reduced at 11°C.…”
Section: Discussionmentioning
confidence: 99%
“…1). The parasite is likely transported from the gut in leucocytes (Rodríguez-Tovar et al 2002), and early merogonic stages have been observed by ISH (Sánchez et al 2001a) or PCR (Sánchez et al 2000) in the heart endocardium a few days after infection. Loma salmonae is first detected in the gills about 2-3 wk p.e.…”
Section: Sequential Developmentmentioning
confidence: 99%
“…The pathogenesis of MGD has recently been elucidated, and the key events include oral uptake of an infectious spore, intragastric spore germination, a brief residence period in the gut lamina propria, and a 2 wk merogony-like phase in the cardiac subendothelium, followed by a macrophagemediated transport of the parasite to the gill where final development (further merogony and sporogony) occurs within gill pillar cells, with sporogony leading to the formation of a distended spore-filled xenoma (Sánchez et al 2000, Rodríguez-Tovar et al 2002. Development to the xenoma stage has been effectively modelled relative to the effects of temperature on the rate of xenoma formation.…”
Section: Introductionmentioning
confidence: 99%